Expedient Synthesis of Highly Functionalised Cyclic Imines - Moss, Thomas A. (Synlett, 2015)
Aryl- and heteroaryl fused cyclic imines are obtained from the starting acetal via a directed metallation–alkylation–condensation sequence using cyclic sulfamidates as the electrophile. A variety of aromatics and heteroaromatics are demonstrated to be applicable to this methodology, which produces highly versatile cyclic imine building blocks for drug discovery and total synthesis programmes.
Keywords: cyclic sulfamidate; metallation; ring opening; alkylation; cyclic imine